2022
DOI: 10.3389/frtra.2022.1035480
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the limits of experimental pancreas transplantation: Working toward the clinical ideal graft

Abstract: Pancreas transplantation is, at present, the only curative treatment for type-1 diabetes that maintains normoglycemia thus avoiding complications arising from poor glycemic control. Despite its great benefits, the number of pancreas transplants has decreased significantly since its inception in the late 1960s, largely due to demographic changes and the consequent suboptimal quality of donors. The selection criteria for pancreas donors mainly depend on morphological variables such as fatty infiltration, fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A systematic review of human and animal's experimental studies showed that ex situ pancreas perfusion reduced ischemic reperfusion injuries, pancreas thrombosis, morbidity of transplantation, and could be a helpful tool to evaluate pancreas prior to transplantation [66]. Normothermic ex situ perfusion with supplemental oxygen replicates near physiological parameters, and seems to be an interesting alternative promising strategy for pancreas organ preservation [68]. However, ideal perfusion parameters are difficult to establish in pancreas transplantation given its complex vascular anatomy and blood flow.…”
Section: Recent Progress and Future Directions 91 New Technologies An...mentioning
confidence: 99%
“…A systematic review of human and animal's experimental studies showed that ex situ pancreas perfusion reduced ischemic reperfusion injuries, pancreas thrombosis, morbidity of transplantation, and could be a helpful tool to evaluate pancreas prior to transplantation [66]. Normothermic ex situ perfusion with supplemental oxygen replicates near physiological parameters, and seems to be an interesting alternative promising strategy for pancreas organ preservation [68]. However, ideal perfusion parameters are difficult to establish in pancreas transplantation given its complex vascular anatomy and blood flow.…”
Section: Recent Progress and Future Directions 91 New Technologies An...mentioning
confidence: 99%
“…In contrast to other solid organs [17], the role of in-situ Normothermic Regional Perfusion after cDCD is emerging whilst ex situ machine perfusion for pancreas and islet transplant is in its infancy. The intrinsic characteristics of the pancreas, with its low blood flow and complex vascular anatomy, makes it highly susceptible to ischemic injury during preservation, resulting in detrimental effects on the organ's microcirculation [18]. This makes the design of the conditions, and the perfusion parameters of machines, more complex than for other solid organs and thus calls for further expert evaluation.…”
Section: Description Of Target Populationmentioning
confidence: 99%